Humanity as Homo Culturus - Mahmoud Dhaouadi (International Institute of Islamic Thought, 2013)
This paper claims that human beings are first of all Homo Culturus and only then Homo Politicus, Homo Sociologus, or Homo Oeconomicus. Human beings are distinguished from all other species by what I call human symbols (HS), namely, language, thought, religion, knowledge/science, myths, laws, and cultural values and norms. As such, they are central to the human identity of individuals, groups, and societies and therefore basic keys for understanding and explaining individual as well as collective behaviors in human societies. The theoretical framework/paradigm of Homo Culturus also helps to explain the phenomenon of the human mind in its various forms: the illiterate mind, the educated mind, and the highly intellectual minds of scientists and scholars such as Ibn Khaldun.